The maid : a novel [book club bag] - Prose, Nita (Prose, Nita. Maid novel, 2022)
"A charmingly eccentric hotel maid discovers a guest murdered in his bed, turning her once orderly world upside down--and inspiring a motley crew of unexpected allies to band together to solve the mystery--in this utterly original debut. Molly Gray is not like everyone else. She struggles with social skills and interprets people literally. Her gran used to interpret the world for her, codifying it into simple rules that Molly could live by. Since Gran died a few months ago, twenty-five-year-old Molly has had to navigate life's complexities all by herself. No matter--she throws herself with gusto into her work as a hotel maid. Her unique character, along with her obsessive love of cleaning and proper etiquette, make her an ideal fit for the job. She delights in donning her crisp uniform each morning, stocking her cart with miniature soaps and bottles, and returning guest rooms at the Regency Grand Hotel to a state of perfection. But Molly's orderly life is turned on its head the day she enters the suite of the infamous and wealthy Charles Black, only to find it in a state of disarray and Mr. Black himself very dead in his bed. Before she knows what's happening, Molly's odd demeanor has the police targeting her as their lead suspect and she finds herself in a web of subtext and nuance she has no idea how to untangle. Fortunately for Molly, a medley of friends she didn't realize she had refuses to let her be charged with murder--but will they be able to discover the real killer before it's too late? A Clue-like, locked-room mystery and a heartwarming journey of the spirit, The Maid explores what it means to be the same as everyone else and yet entirely different--and reveals that all mysteries can be solved through connection to the human heart"--